Wound-directed revascularisation in the Diabetic Foot patients - N. Kononenko; A. Sheikhali (Kazimierz Wielki University, 2016)
Introduction: Peripheral arterial diseases in patients with diabetic foot have significant features in pathogenesis, manifestations and course compared with peripheral arterial disease. These features require different approaches to treatment and the the angiosome theory can help increase the effectiveness of revascularization in patients with diabetic foot. The aim: Analyse the results of revascularisation of lower extremity arteries in the patients with ischemic diabetic foot ulcers according to the angiosome theory. Materials and metods: We analysed 98 revascularisations of arteries of 77 lower limbs in 74 ischemic diabetic foot patients for the period from 2017 to 2021. Angioplasties were performed in 71 cases (72,5%), open operations - in 21 (21,4%), hybrid operations - 6 (6,1%). According to angiosome theory we divided the revascularizations into two groups. І group - direct revascularizations (DR) - 57 cases, ІІ group - indirect revascurizations (IR) - 21 cases. Results: Within 6 months foot lesions healing fixed in І group (DR) - 81.7%, in ІІ group (IR) - 78.6%. Major amputations were the consequences of 17,1% revascularizations: DR group - 12,4%, IR group - 33,3%. Functional capacity of the lower extremity within one year was saved in 79,3% in DR group and in 57,9% in IR group. Repeated revascularizations accounted for 21,4% of cases: in DR group - 20,5%, in IR group - 25%. The results of the statistical analysis revealed the dependence of the risk of amputation on adherence to angiosome theory during revascularization. Conclusions: Angiosome-targeted revascularization in the area of foot lesions increases efficiency of the revascularization and improves immediate and long-term treatment results.